Animal models for oral transmission of Listeria monocytogenes - D'Orazio, Sarah E. (Frontiers in Cellular and Infection Microbiology, 2014)
Listeria monocytogenes has been recognized as a food borne pathogen in humans since the 1980s, but we still understand very little about oral transmission of L. monocytogenes or the host factors that determine susceptibility to gastrointestinal infection, due to the lack of an appropriate small animal model of oral listeriosis. Early feeding trials suggested that many animals were highly resistant to oral infection, and the more reproducible intravenous or intraperitoneal routes of inoculation soon came to be favored. There are a fair number of previously published studies using an oral infection route, but the work varies widely in terms of bacterial strain choice, the methods used for oral transmission, and various manipulations used to enhance infectivity. This mini review summarizes the published literature using oral routes of L. monocytogenes infection and highlights recent technological advances that make oral infection a more attractive model system.